2020
DOI: 10.1111/vcp.12823
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognizedAnaplasmasp. in erythrocytes from Gopher Tortoises (Gopherus polyphemus)

Abstract: Background In 2015, a previously unrecognized intracytoplasmic erythrocytic inclusion was discovered in anemic wild‐caught adult gopher tortoises (Gopherus polyphemus). Subsequently, molecular diagnostics revealed this inclusion to be a novel Anaplasma sp. Objectives The goal of this study was to morphologically characterize these erythrocytic inclusions by light and transmission electron microscopy (TEM). Methods Blood samples were taken from two car‐injured wild‐caught gopher tortoises for the preparation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The morphologic characteristics of the intra-erythrocytic inclusions observed via light microscopy and TEM in the present case were most consistent with the previously published characteristics of Anaplasma spp., particularly those described in a recent report by Raskin et al, which detailed the microscopic characterization and PCR confirmation of a novel Anaplasma species found within erythrocytes of two anemic, wild gopher tortoises (G polyphemus) in Florida. 2 The order Rickettsiales comprises three families, consisting of Rickettsiaceae, Midichloriaceae, and Anaplasmataceae, with the family Anaplasmataceae composed of five recognized genera including Aegyptianella, Anaplasma, Ehrlichia, Neorickettsia, and Wolbachia. 3 Members of the genus Anaplasma are Gram-negative, non-motile, obligate intracellular bacteria that replicate by binary fission and are found within membrane-bound inclusions inside the cytoplasm of vertebrate and invertebrate host cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The morphologic characteristics of the intra-erythrocytic inclusions observed via light microscopy and TEM in the present case were most consistent with the previously published characteristics of Anaplasma spp., particularly those described in a recent report by Raskin et al, which detailed the microscopic characterization and PCR confirmation of a novel Anaplasma species found within erythrocytes of two anemic, wild gopher tortoises (G polyphemus) in Florida. 2 The order Rickettsiales comprises three families, consisting of Rickettsiaceae, Midichloriaceae, and Anaplasmataceae, with the family Anaplasmataceae composed of five recognized genera including Aegyptianella, Anaplasma, Ehrlichia, Neorickettsia, and Wolbachia. 3 Members of the genus Anaplasma are Gram-negative, non-motile, obligate intracellular bacteria that replicate by binary fission and are found within membrane-bound inclusions inside the cytoplasm of vertebrate and invertebrate host cells.…”
Section: Discussionmentioning
confidence: 99%
“…A marginale and tends to have a more aggressive clinical course. 4 Mammals are the predominant vertebrate host for Anaplasma, but a recent report by Vanstreels et al suggests that birds can also serve as competent hosts, as evidenced by an African penguin (Spheniscus demersus) with erythrocytes that contained inclusions strikingly similar to those described by Raskin et al 2 Other organisms to consider, particularly in birds and reptiles that are similar in appearance to Anaplasma morulae with round, purple, membrane-bound inclusions 2-4 µm in diameter, are those of genus Aegyptianella (AE). The most notable species is Aegyptianella pullorum in birds, transmitted by the soft tick Argas persicus to various avian species, including chickens, turkeys, ducks, geese, and quails over a wide geographic distribution, including North America, South America, Europe, Africa, and Asia.…”
Section: However Initial Infection With a Centrale Provides Immunity Againstmentioning
confidence: 90%
See 2 more Smart Citations
“…In the present study, the blood smear examination also demonstrated the presence of intraerythrocytic dark purple microorganisms appearing as coccoid-and pear-shaped. The coccoid-shaped intraerythrocytic parasites were generally identified as Anaplasma, bacteria belonging to the order Rickettsiales, whereas the pear-shaped microorganisms were generally identified as Babesia, protozoa belonging to the order Piroplasmida [18][19][20][21]. The genus and species of these blood parasites remain unidentified as of now.…”
Section: Discussionmentioning
confidence: 99%